An exploratory investigation of sexual health screening in the first 12 weeks of case management in populations with severe mental illness. (12th September 2016) - Corbett, Rebecca; Elsom, Stephen; Sands, Natisha; Prematunga, Roshani
Abstract: The sexual health of people with mental illness is commonly overlooked, neglected or inadequately addressed in mental health care, despite evidence showing that people with severe mental illness are more vulnerable to sexually transmitted infections (including HIV), sexual side‐effects, and sexual dysfunction than the general population. This article reports a study that investigated sexual health screening in five community mental health clinics within a large a regional health service in Victoria, Australia. The aim of the study was to examine the extent to which sexual health screening is currently undertaken on newly admitted case‐managed consumers, and to identify the types of screening undertaken. An exploratory design using retrospective file audit was used in the study. A total of 186 medical records met the study inclusion criteria. The study found that less than 40% of consumers were provided with sexual health screening during their first 12 weeks of case management. The study also found that sexual side‐effects, issues of fertility, sexual self‐esteem, safe sexual practices, and sexual dysfunction were rarely screened for. Poor sexual health screening has implications for the safety and quality of mental health care and requires targeted research to improve understandings and approaches to care.